PENYULUHAN POLA MAKAN MENGURANGI KEJADIAN KURANG ENERGI KRONIS PADA WANITA USIA SUBUR - Irni Setyawati; Dian Soekmawati Riezqy Arienda; Sri Handayani; Kusniyati Utami; Sarah Husyanti (Stikes Yarsi Mataram, 2023)
Chronic Energy Deficiency (CED) often affects women of childbearing age. The Local Area Monitoring Report of mothers for Karang Pule Health Center in November 2021 found 5.74% (19 people out of 73 pregnant women) experienced The purpose of this service was to increase awareness and the eating behavior of women of childbearing age.The service activity